Pengembangan Media Pembelajaran Interaktif Berbasis Smart Apps Creator Mata Pelajaran IPAS Kelas IV SDN 14 Pontianak Selatan - Ririn, Elisia Rania; Salimi, Asmayani; Ghasya, Dyoty Aulia Vilda (AS-SABIQUN, 2024)
This study aims to produce a product in the form of interactive learning media based on Smart Apps Creator for the IPAS subject that is deemed suitable for use. The Research and Development (R&D) method is employed, adapting the Borg & Gall development method, which includes only 7 stages: research and data collection, planning, initial product development, initial field testing, main product revision, field testing, and operational product revision. This research involves both qualitative and quantitative approaches. Data collection methods include interviews, documentation, validator validation questionnaires, and questionnaires during field testing. The results indicate that during the development process of interactive learning media based on Smart Apps Creator, these seven stages were successfully executed. The language aspect's feasibility, with the highest percentage value at 83%, falls into the "Very Good" category. Furthermore, the validation results from experts show a percentage value of 80%, categorized as "Good". The design aspect's feasibility obtains a percentage value of 86.39%, falling into the "Very Good" category, while the results of validity testing by experts show a percentage value of 85.93%, also falling into the "Very Good" category. Meanwhile, the feasibility of the content aspect obtains a percentage value of 88%, which falls into the "Very Good" category, and the results of validity testing by experts show a percentage value of 80%, categorized as "Good". Based on the obtained results, it can be concluded that the developed educational game media for the sixth-grade Science subject at SD Negeri 14 Pontianak Selatan is considered suitable for use in the teaching and learning process.